Analysis of Factors Related to Family Assistance of People with Schizophrenia - Doris, Doris; Budiati, Endang; Rahayu, Dewi; Adyas, Atikah; Karyus, Aila (Indonesian Journal of Global Health Research, 2024)
Schizophrenia is a complex chronic mental health. The role of family is very important in fulfilling basic needs, the cost of maintaining the, treatment and prevention a recurrence. In the onion, often still found the stigma and discrimination, and poor family assistance in patients, that is allegedly affected by low support officers to educate.Objective: Research objectives and analyze factors associated with assistance schizophrenic Method: kind of research with a quantitative approach cross sectional. The population research even all patients with schizophrenia and a 590, sample is 247 respondents. Simple random sampling techniques of sampling, analisis Data using univariate, bivariate and multivariate analysis using logistic regression tests. Results: is a knowledge of the known with p-value 0,016 (<0,05 & OR 2.248), p-value attitude 0,040 (<0,05 OR 2.04), the role of health workers p-value 0,004 (< 0,05 & OR 2.612), access to information p-value 0,028 (<0,05 & OR 2.110), the family motivation p-value 0,009 (<0,05 & OR 2.404). The dominant factor associated with the role of family assistance schizophrenic health workers with p-value 0,002 & OR 2.793. Conclusions Advice to improved access and coordination services, promoting access to mental health services, facilitate coordination between health workers, help family in navigating the health care system.